Phenological growth stages of torch ginger (Etlingera elatior) inflorescence - Choon, Sea Yeat; Ding, Phebe; Tengku Muda Mohamed, Mahmud; Shaari, Khozirah (Universiti Putra Malaysia Press, 2016)
Torch ginger (Etlingera elatior) inflorescence with its showy appearance can be used as a cut flower. However, the development of inflorescence has not been studied. The aim of this study is to determine the phenological stages of torch ginger inflorescence from the emergence of rhizome until full bloom stage using the extended BBCH scale. The growth stages of the inflorescence are categorised into peduncle elongation, inflorescence emergence, flowering and senescence. It takes about 60 days for the inflorescence to emerge from rhizome and develop to reach full-bloom stage with true flower opening. This study provides important information in understanding this crop.